Embedded FreeBSD cookbook - Cevoli, Paul. (Oxford : Newnes, 2003)
The FreeBSD operating system has become a popular OS choice for embedded systems due to its small size and the fact that it is free to users. However, detailed information on using FreeBSD is difficult to find. Author Paul Cevoli, an experienced embedded systems engineer, answers that need in this cookbook aimed at making life easier for engineers working with FreeBSD. Topics covered in the book include core operating system components, processes, process scheduling, virtual memory, device drivers and debugging, as these are the core features necessary for embedded system developers. The core software provided to the reader on the accompanying CD-ROM is written in C. Each chapter discusses basic components of FreeBSD, device drivers, Unix kernel, and C and GNU development tools, and provides the reader with the information needed to accomplish the stated task, along with sample source code. * Provides numerous examples of system software with source code and debugging techniques that can provide starting points for your own designs * Covers core operating system components, processes and process scheduling, system booting, virtual memory, device drivers, debugging, and much more * All sample code is provided on the accompanying CD-ROM, along with other useful programming tools.
System Calls; Processes; Signals; Process Scheduling; Interprocess Communication; Virtual Memory; I/O Subsystem; Device Drivers; Building the FreeBSD Kernel; System Booting; Kernel Debugging using GDB.
Includes index.
Keywords: FreeBSD; Operating systems (Computers).; Embedded computer systems; Electronic books